(untitled) (The Pakistan Development Review, 2012)
The idea that trade is important for economic growth dates back to the nineteenth century when classical economists like Adam Smith, Ricardo, John Stuart Mill etc. advocated the favourable effects of international trade on output. Since then a rich body of both theoretical and empirical literature has evolved with regards to exports and trade policy. Within this overall literature, two competing approaches that can be broadly identified are Import Substitution industrialisation (IS) and Export-Led (EL) growth. According to the EL growth hypothesis, exports can promote economic growth through three main channels that are as follows: (i) trade enables firms (at the micro level) and countries (at the macro level) to gain through specialisation and economies of scale. The most efficient producers witness increasing market shares, that in turn lead to aggregate productivity gains through a reallocation of resources [Taylor (1981) and Melitz (2003)], (ii) Exports are an important source of foreign exchange. These resources are important not just for the purchase of vital inputs such as capital and machinery but are extremely valuable where balance of payments constraints are widespread [Faridi (2012)]. (iii) Trade is an important source of knowledge and technological transfers. New growth theory has shown that trade with technologically innovative countries allows access to the technological know-how of trading partners, and also has the potential of encouraging innovative activity by increasing the returns to innovate as traders have access to a larger market relative to non-trading firms.